Services trade and labour market outcomes - Lassmann, Andrea (OECD Trade Policy Papers, 2020)
This report draws on individual-level and firm-level data to better understand the relationships between services trade and labour market outcomes. It seeks to shed light on how firms benefit from the rise in services trade, which groups of workers are affected the most, how employment and wages adjust to increased services trade, and the impact of policy settings on outcomes in these areas. It relies on new empirical analyses undertaken on the European Union, Brazil, India, Italy, Slovenia, Sweden, the United Kingdom, and Viet Nam together with insights from economic literature and a meta-analysis of the results underlying this report. Findings suggest that firms' importing, offshoring and exporting activities are generally associated positively with firm employment in advanced and emerging market economies, although the relationship is more uncertain for the latter group of countries. Firm's overall wage responses to services trade are on average positive as well, but quantitatively small. Looking at the distributional impact, there is mixed evidence for a skill bias in wages related to increased services exports and imports. Women are found to benefit from services export growth, while increased imports are estimated to exert downward pressure on the wages of women compared to the ones of men